Editing video cases to facilitate preservice teachers' self-reflection on their instructional decisions. Issue 4 (4th July 2022) - Sancar, Raziye; Deryakulu, Deniz
ABSTRACT: This study examines preservice teachers' (PTs') video case (VC) editing process to enhance their self-reflection on instructional decisions in teaching experiences. We apply the triple-cycle process, including teaching experiences, video editing, and peer discussion. Each PT edited three teaching experiences and discussed a total of forty-eight VCs. While editing VCs, PTs tended to notice, describe, identify the reason, judge, express emotions, analyse, and generalize with any other situations. The results indicated that while editing their teaching experiences, PTs improved self-reflection on their instructional decisions, which increased from defining to analysing and generalizing the instructional decisions. Editing video-cases improve PT's self-reflection on their instructional decisions. Viewing and discussing peers' experiences enrich PT's teaching repertoire. PT tend to focus on how to teach including classroom management and teaching methods. Editing and discussing video-cases enhance PT's noticing skills from both the teacher's and the student's perspectives. Thereby, editing video-cases and viewing and discussing peers' experiences improved PT's self-reflection and the ability to notice through the eyes of both the student and the teacher. And it also enriched PT's teaching repertoire.